The level of knowledge of certain groups of women about the menopause period - Wyderka, Mieczysława; Zdziennicki, Andrzej; Byalek, Tetyana (Menopause Review/Przegląd Menopauzalny, 2007)
The entire analysis included 320 women living in the city cities of York, Lodz and Ternopil. The gathered material has been divided into groups: teachers, nurses, office workers and women with basic education. Our research shows that the educational level of women in this study has a major influence on their knowledge about the term of menopause, its symptoms, understanding the deficiency of female hormones in the body, and usage of hormonal substitute therapy. Nurses of York and Lodz proved to have the most extensive knowledge on the subject of this research. 16.7% of women living in the city of York, 15% of Lodz and 20% of Ternopil have used hormonal substitute therapy. 68.3% of women of York and 79.2% of Lodz stated that their knowledge is superficial and requires completion. Similar opinions were stated by 50% of women living in the city of Ternopil. The women from Ternopil seemed to have better healthy lifestyle awareness than those from of York and Lodz.